2011
DOI: 10.14475/kjhpc.2011.14.3.144
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Attitudes of Nursing Students toward Death, Self-esteem and Life Satisfaction according to Clinical Experience

Abstract: Purpose: This study was conducted to compare nursing students' attitudes toward death, self-esteem and life satisfaction according to clinical experience. Methods: We surveyed 1,030 nursing students from two different universities with a questionnaire consisting of items regarding attitudes toward death, self-esteem and life satisfaction. The data were analyzed using a PASW program. Results: Students with clinical experience scored 2.85 on the attitude toward death, while those without clinical experience scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Another comparison study by Kim, Kim and Son (2011) on nursing students' attitudes toward death, self-esteem, and life satisfaction according to clinical experience also had been done. This study revealed that students with clinical experience had significantly higher self-esteem and life satisfaction than those without it.…”
Section: Nursing Students' Clinical Experiencementioning
confidence: 99%
“…Another comparison study by Kim, Kim and Son (2011) on nursing students' attitudes toward death, self-esteem, and life satisfaction according to clinical experience also had been done. This study revealed that students with clinical experience had significantly higher self-esteem and life satisfaction than those without it.…”
Section: Nursing Students' Clinical Experiencementioning
confidence: 99%